Regulation of cellular diacylglycerol through lipid phosphate phosphatases is required for pathogenesis of the rice blast fungus, Magnaporthe oryzae. - Md Abu Sadat (Public Library of Science (PLoS), 2014)
Considering implication of diacylglycerol in both metabolism and signaling pathways, maintaining proper levels of diacylglycerol (DAG) is critical to cellular homeostasis and development. Except the PIP2-PLC mediated pathway, metabolic pathways leading to generation of DAG converge on dephosphorylation of phosphatidic acid catalyzed by lipid phosphate phosphatases. Here we report the role of such enzymes in a model plant pathogenic fungus, Magnaporthe oryzae. We identified five genes encoding putative lipid phosphate phosphatases (MoLPP1 to MoLPP5). Targeted disruption of four genes (except MoLPP4) showed that MoLPP3 and MoLPP5 are required for normal progression of infection-specific development and proliferation within host plants, whereas MoLPP1 and MoLPP2 are indispensable for fungal pathogenicity. Reintroduction of MoLPP3 and MoLPP5 into individual deletion mutants restored all the defects. Furthermore, exogenous addition of saturated DAG not only restored defect in appressorium formation but also complemented reduced virulence in both mutants. Taken together, our data indicate differential roles of lipid phosphate phosphatase genes and requirement of proper regulation of cellular DAGs for fungal development and pathogenesis.